New constraints on the age and style of continental breakup in the South Atlantic from magnetic anomaly data - Collier,JS; McDermott,C; Warner,G; Gyori,N; Schnabel,M; McDermott,K; Horn,BW (Earth and Planetary Science Letters, 2017)
We present new constraints on the opening of the South Atlantic Ocean from a joint interpretation of marine magnetic anomaly grids and forward modelling of conjugate profiles. We use 45,000 km of recently collected commercial ship track data combined with 561,000 km of publically available data. The new data cover the critical ocean–continental transition zones and allow us to identify and downgrade some poorly navigated older ship tracks relied upon in earlier compilations. Within the final grids the mean cross-over error is 14 nT computed from 8,227 ship track intersections. The forward modelling used uniformly magnetised bodies whose shapes were constrained from coincident deep-seismic reflection data. We find the oldest magnetic anomalies to date from M10r (134.2 Ma, late Valanginian) north of the Falkland-Agulhas Fracture Zone and M3 (129.3 Ma, Barremian) south of the Rio Grande Fracture Zone. Hence, assuming the GPTS used is correct, continental breakup was contemporaneous with the Parana and Etendeka continental flood basalts. Many of the landward linear anomalies overlap seismically mapped Seaward Dipping Reflectors (SDRs). We interpret this to mean that a significant portion of the SDRs overlay crust formed by subaerial seafloor spreading. Here crustal accretion is envisaged to be similar to that at mid-ocean ridges, but sheet lava flows (that later form the SDRs) rather than pillow basalts form the extrusive component. Segmentation of the linear anomalies generated implies that this stage of continental breakup is organised and parallels the seafloor spreading centre that follows. Our results call into question the common assumption that at volcanic continental margins the first linear magnetic anomalies represent the start of conventional (submarine) oceanic crustal generation.